The responsibility of citizens in the good performance of public administration: the case of the Ombudsman's Office in Costa Rica (National Administration Journal, 2023)
This essay analyzes the responsibility that Costa Rican citizens have with the ignorance of the Ombudsman’s Office. The Law creating this body (Law 7319) allows the inhabitant affected by negligence or omission to denounce the hierarch for breach of duties, either before the Legislative Assembly or before the competent jurisdictional, for this reason, the Legislator did not grant any immunity to whoever holds the position of Ombudsman of the Inhabitants when issuing the creation law. The hermeneutic method was used to analyze and interpret the texts, and build a constructive and permanent dialogue.
Keywords: Ombudsman’s office; human rights; citizen responsibility and public administration